2022
DOI: 10.1080/02670844.2022.2087955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In2(SO4)3 on characteristics of Al–Li alloy MAO coating

Abstract: Micro arc oxidation (MAO) coatings were prepared on the surface of 2195 Al-Li alloy by adding different amounts of indium sulphate (In 2 (SO 4 ) 3 ) into an electrolyte consisting of silicate and phosphate. The surface, cross section, phase composition, and electrochemical experiments of MAO coatings were analysed. X-ray diffraction results show that the coating was composed of γ-Al 2 O 3 , α-Al 2 O 3 , and In 2 O 3 . The results show that after adding In 2 (SO 4 ) 3 , the discharge holes on the surface of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…2), the coating's resistance raised, causing the voltage to climb. 12,18 Meanwhile under the influence of the electric field, negatively charged Er 2 O 3 formed from Er 3+ was easily adsorbed on the surface of the coating and increasing resistance, causing the increase in voltage. 19,20 However the voltage dropped from 492 V to 465 V at the Er 2 (SO 4 ) 3 of 0.20 g L −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2), the coating's resistance raised, causing the voltage to climb. 12,18 Meanwhile under the influence of the electric field, negatively charged Er 2 O 3 formed from Er 3+ was easily adsorbed on the surface of the coating and increasing resistance, causing the increase in voltage. 19,20 However the voltage dropped from 492 V to 465 V at the Er 2 (SO 4 ) 3 of 0.20 g L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…810 Electrical parameters, oxidation period, electrolyte, and additives all have an impact on the coating performance. 11,12 Related research had demonstrated that adding the rare earth element Er to titanium alloys can enhance the alloy's overall performance. Y.K.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, aluminium-lithium alloy is easily corroded by Cl − , H + and other corrosion medium, due to the active lithium element, causing corrosion hazards such as pitting and intergranular corrosion, which restricts the application expansion of aluminium-lithium alloy in aerospace [3,4]. The corrosion resistance of aluminium-lithium alloy can be enhanced by surface-treatment technologies, including anodizing [5], shot peening [6] and MAO [7]. Compared with conventional anodizing and shot peening, MAO technique has become a research hotspot because of its simple process, environmental-friendly and excellent corrosion resistance of its products.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, additives are regarded as a key factor. Research shows that adding rare earth oxides or rare earth salts into the electrolyte can improve surface characteristics and corrosion protection of coatings, such as Y 2 O 3 particles, indium sulphate and so on [7,14]. So far, the research on doping scandium nitrate into MAO coating of 2195 aluminium-lithium alloys has not been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma electrolytic oxidation (PEO) is a ceramic film-grown process on the surfaces of Al, Mg, Ti, Zr, Ta and other valve metals operating at a specific working voltage and in specific electrolyte solution, accompanied by transient high temperature and high pressure of plasma discharge [17][18][19][20]. The surface of the oxide film produced by PEO usually presents a sparse and hole-containing appearance, which can provide migration paths for Li + diffusion when the film acts as the electrode for LIBs.…”
Section: Introductionmentioning
confidence: 99%